2022
DOI: 10.1038/s44159-022-00081-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and consequences of intellectual humility

Abstract: In a time of societal acrimony, psychological scientists have turned to a possible antidote — intellectual humility. Interest in intellectual humility comes from diverse research areas, including researchers studying leadership and organizational behaviour, personality science, positive psychology, judgement and decision-making, education, culture, and intergroup and interpersonal relationships. In this Review, we synthesize empirical approaches to the study of intellectual humility. We critically examine dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 148 publications
0
83
0
Order By: Relevance
“…Under this model, a person generalizes their lack of knowledge of one phenomenon to other phenomena. This could represent a temporary boost to intellectual humility (Porter et al, 2022) where after attempting (and failing) to explain something, people might recognize the extent of their ignorance about that phenomenon (Meyers et al, 2020), which they then generalize to their knowledge of other phenomena as well. For instance, failing to explain how a speedometer works might lead someone to question their knowledge of how snow forms because the person attributes a general feeling of ignorance to the rest of what they think they know.…”
Section: Discussionmentioning
confidence: 99%
“…Under this model, a person generalizes their lack of knowledge of one phenomenon to other phenomena. This could represent a temporary boost to intellectual humility (Porter et al, 2022) where after attempting (and failing) to explain something, people might recognize the extent of their ignorance about that phenomenon (Meyers et al, 2020), which they then generalize to their knowledge of other phenomena as well. For instance, failing to explain how a speedometer works might lead someone to question their knowledge of how snow forms because the person attributes a general feeling of ignorance to the rest of what they think they know.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a positive attitude toward oneself and others may distinguish intellectually humble people. Moreover, previous studies have shown that intellectual humility is positively associated with variables that form the essence of a positive outlook, such as life satisfaction, 62 , 63 self-esteem 18 and optimism, 28 but there is no research investigating the relationship between intellectual humility and positive orientation.…”
Section: Methodsmentioning
confidence: 99%
“…Epistemic humility (also referred to as intellectual humility by some researchers)-the meta-cognitive ability to acknowledge the strengths and limits of one's knowledge of the human experience-is also an important component of wisdom (Nusbaum & Schneider, 2020). While SELF-TRANSCENDENCE & WISE REASONING 5 some measures of wise reasoning include items that measure the recognition of one's own intellectual fallibility in interpersonal conflicts (Grossmann et al, , 2020, epistemic humility has also been theorized and studied as an intellectual virtue on its own (e.g., Dormandy, 2018;Porter, Baldwin et al, 2022;Porter, Elnakouri et al, 2022;Tanesini, 2018;Whitcomb et al, 2017). Socrates suggested intellectual virtues, like epistemic humility, would be at the heart of wisdom (Ryan, 2020).…”
Section: Going Beyond Ourselvesmentioning
confidence: 99%